Migration of the retained intracranial bullet to the spinal canal: A case report - Lepić, Milan; Minić, Ljubodrag; Stefanović, Slaviša; Novaković, Nenad; Lokaj, Aleksandra; Pavlićević, Goran (Vojnosanitetski pregled, 2021)
Introduction. Retained intracranial missiles migration is rarely reported. Most of the time, the missile will migrate and remain intracranially, but in extremely rare cases, it may reach the spinal canal. The aim of the study was to present a patient with this rare clinical entity. Case report. The 29-years-old male suffered from the gunshot wound to the head through the left external auditory meatus. The bullet was located in the posterior fossa. Initial debridement without bullet removal was performed. Four months after the injury, the patient came back complaining of neck stiffness and progressive weakness of all extremities. Plain radiography revealed the bullet in the spinal canal at the level of C2 vertebra and computed tomography confirmed localization in the posterior aspect. An emergency procedure was performed for bullet removal and spinal cord decompression. Conclusion. The bullets tend to migrate. Migration to the spinal canal is rare, but takes a significant risk, due to the potential secondary injury. The removal of a bullet at-all-costs may not be justified. However, the prediction of migration based on the predisposing factors would be of great value to treating these patients adequately.
Keywords: head injuries, penetrating; neurosurgery; spinal cord compression